Accretion-outflow connection in the outliers of the "universal" radio/X-ray correlation - Coriat, M.; Corbel, S.; Prat, L.; Miller-Jones, James; Cseh, D.; Tzioumis, A.; Brocksopp, C.; Rodriguez, J.; Fender, R.; Sivakoff, G. (2010)
In recent years, numerous efforts have been devoted to unravel the connection between accretion flow and jets in accreting compact objects. Here we report new constraints on these issues, through the long term study of the radio and X-ray behaviour of the black hole candidate H 1743-322. This source is known to be one of the "outliers" of the universal radio/X-ray correlation, i.e. a group of stellar mass accreting black holes displaying fainter radio emission for a given X-ray luminosity, than expected from the correlation. In this work we find, at high X-ray luminosity in the hard state, a tight radio/X-ray correlation with an unusual steep slope of b = 1.38 ± 0.03. This correlation then breaks below ~ 5 × 10-3L Edd (M/10M)-1 in X-rays and becomes shallower. When compared with radio/X-ray data from other black hole X-ray binaries, we see that the deviant points of H 1743-322 join the universal correlation and seem to follow it at low luminosity. Based on these results, we investigate several hypotheses that could explain both the b ~ 1.4 slope and the transition toward the universal correlation. © International Astronomical Union 2011.